The Association Between Clinical Signs and Detection of Congenital Heart Disease by Echocardiography in Neonates: Systematic Review - Almarshud, Saad; Ali, Mohd Hanafi (Journal of Neonatal Surgery, 2025)
Background: Background and objective: Congenital heart disease (CHD) is a leading cause of death in newborns. Accurate clinical examination of neonates and careful auscultation of the heart along with timely echocardiography plays an important role in early diagnosis of heart diseases and starting treatment measures. This systematic review aimed to evaluate the correlation and diagnostic value of clinical signs in predicting echocardiographic findings in neonates. Patients and Methods: This systematic review was conducted based on PICO Format study design questions according to PRISMA guidelines. A comprehensive search of online databases was conducted, including Scopus, PubMed, and Cochrane Library. Full text, English language, peer-reviewed, prospective and retrospective cohort, observational and cross-sectional articles were included if they evaluated the correlation and diagnostic value of clinical signs in predicting echocardiographic findings in neonates. Main Findings and conclusion: A significant proportion of neonates presenting with heart murmurs or cyanosis had CHD on echocardiography. Ventricular septal defect and patent ductus arteriosus were the most commonly diagnosed anomalies. Clinical examination showed moderate-to-high sensitivity and specificity in detecting CHD. However, echocardiography significantly improved diagnostic accuracy. While targeted echocardiography in symptomatic neonates proved beneficial, routine screening in asymptomatic neonates was associated with an increased rate of clinically insignificant findings. Echocardiography should be employed in neonates with heart murmurs or cyanosis for early detection of CHD. A clinically guided approach is recommended over routine screening to avoid over-diagnosis and unnecessary interventions